Effect of Polypropylene Grafted Maleic Anhydride (PP-G-MAH) on the Properties of Asphalt and its Mixture Modified With Recycled Polyethylene/Recycled Polypropylene (RPE/RPP) Blends - Zhang, Wencai; Hao, Xiaogang; Fan, Changxin; Zhang, Shuai; Ma, Dechong; Yu, Xiaofang; Fu, Zhaohua; Feng, Gongji (Frontiers in Materials, 2022)
In this study, a ternary blend modifier (TBM) was prepared with RPE, RPP and various dosage of PP-g-MAH (i.e. 0%, 1%, 3%, 5%, 7% and 9% by weight of RPE and RPP) by a twin-screw extruder. The performance of TBM (4% by weight of asphalt) modified asphalt was studied, with the increase of PP-g-MAH content, the penetration decreases gradually, but softening point and viscosity increases and ductility exists minimum value at 7% content, with the increasing of PP-g-MAH percentage, the dynamic rheological properties shows that |G*| increases, while the δ and |G*|cosδ decrease, and the fatigue performance (|G*|sinδ) of TBM modified asphalt is worse than virgin asphalt. Dynamic stability test shows that TBM is quite prominent to high temperature properties of modified asphalt mixture. BBR test indicates that m-value of asphalt modified with TBM doesn't fulfill the requirements (m-value>0.3) except 5% and 7%, but the S meets the standard requirements ( S<300MPa), and increases from 0% to 7%, then decreases slightly. In order to illuminate possible reasons, chemical reaction (ester compounds generated) and physical twines concerned polymer molecules were put forward, and the results were confirmed by infrared analysis.